Funding Structure and Financial Performance. Empirical Study in Savings and Credit Cooperatives of Segment 1 in Ecuador - Oñate-Paredes, Carlos Andrés (2022)
This research, applied to savings and credit cooperatives (COAC) in segment 1 of Ecuador, aims to analyze the relationship between funding structure and financial performance in a period prior to the start of the COVI-19 pandemic. For this purpose, the Panel Corrected Standard Errors Estimator (PSCE) was used. The information was obtained from the Superintendence of Popular and Solidarity Economy of Ecuador (SEPS) and from the websites of each COAC, generating a database composed of three matrices: the first related to the funding structure, the second with the characteristics COAC and the third with macroeconomic variables. The main results point to a positive, but not statistically significant, impact of wealth on financial self-sufficiency. On the other hand, it was shown that the financial resources of the public with higher cost negatively influence the performance of the COACs, suggesting the need for a less onerous funding structure for the cooperatives.